Implementation of Digital Media in Learning Indonesian Language in Class IV MI Al Islam Majasem Purbalingga - Prihatin, Metros (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The Indonesian language subject is one of the subjects that is indispensable in the world of education and has a major role in the growth of science, culture, social and the expression of students' feelings. Indonesian is the national language and as a formal language used in all fields. At the elementary school/madrasah Ibtidaiyah level, the competencies that must be mastered by students in this learning include students being able to read, understand reading, both in the form of text, and those presented in non-text form. It is not an easy thing, to do "transferring" subject matter, because the abilities of students are different. Therefore, we need an appropriate media so that Indonesian is in demand and the desired purpose is achieved. In this case the author will use digital media in learning Indonesian in class IV MI Al Islam Majasem. This study aims to describe and analyze the use of digital media used in learning Indonesian in class IV MI Al Islam Majasem. This study uses a qualitative description method. The results of this study are the digital media used in learning Indonesian, namely audio-visual media from youtube video, google classroom application, voicenote application, whatsapp group and digital power point media.